Pharmacist counseling intervention to improve patient antibiotic compliance - I Gusti Ayu Rai Widowati; I Made Ady Wirawan; Ni Made Sri Nopiyani; Komang Ayu Kartika Sari (Public Health and Preventive Medicine Archive, 2018)
Background and purpose: Reported microbial resistance to antibiotics is increasing. One of the main factors is patient noncompliance in use of antibiotics. The purpose of this study was to determine the effectiveness of pharmaceutical counseling in a pharmacy setting to increase compliance with antibiotic use. Methods: A randomized controlled trial was conducted on 104 adult patients aged 18 years and over who purchased antibiotics by prescription at a pharmacy in Denpasar City, Bali Province. Subjects were divided into intervention and control groups using block randomization method. The intervention group was provided with pharmaceutical counseling by a pharmacist, while the control group was provided drug information according to the pharmacy service standard. Subject compliance was measured by telephone interview using the Morisky Medication Adherence Scale-8 questionnaire within 3-5 days after purchasing the medication. Statistical analysis with the Mann Whitney U Test was performed to determine the difference in mean rank of compliance scores. Logistic regression analysis was conducted to determine the adjusted compliance ratio. Results: The number of subjects analyzed was 98, as five subjects could not be contacted by telephone and one subject was hospitalized. The mean rank of compliance scores in the intervention group (61.05) was significantly higher (p<0.01) than the comparison group (37.95). The proportion of compliance in the intervention group was 65.3% and the control group was 18.4%, with the proportion ratio (PR) of 3.56 (95%CI: 1.90- 6.64). Logistic regression analysis showed that variables which significantly increased compliance with antibiotic use were pharmacist counseling (APR=9.33; 95%CI: 3.24 26.87), frequency of taking medication (APR=6.94; 95%CI: 2.01-23.92) and method of payment (APR=4.30; 95%CI: 1.18-15.66). Conclusion: Pharmaceutical counseling at a pharmacy setting was found to increase compliance of antibiotic use. Compliance of antibiotic use is also influenced by the frequency of taking medication and the method of payment. Pharmacist counseling when accessing medication at a pharmacy is crucial for improving patient compliance of antibiotic use.